Blood pressure recording in children. Issue 249 (October 1971) - Long, M.; Dunlop, J. R.; Holland, W. W.
Abstract : Blood pressure levels for 148 children aged 0-14 years were recorded. Two different methods of measurement (the standard sphygmomanometer and the random-zero machine) and two cuffs of varying size were used on each child. Measurements of arm size and pulse rate were taken, and an assessment was made of the emotional state of each child: no association was found between these factors and the recorded measurement of blood pressure. The experiment does however show that: (1) the effect of cuff size can be minimized by using the largest cuff that will fit the child, and then applying a standard correction to the measurement taken; and (2) the random-zero machine is a preferable method of measurement as it reduces observer bias, though measurements taken with a standard and a random-zero machine are not directly comparable.